2017
DOI: 10.1093/jscr/rjx067
|View full text |Cite
|
Sign up to set email alerts
|

Isolated dilatation of the cystic duct-Type VI choledochal cyst: a rare case presentation and review of the literature

Abstract: An isolated cystic dilatation of the cystic duct is extremely rare and very few cases have been reported in the world literature. The existing Todani's classification does not include this as a separate entity and thereby, it has been vaguely termed as a Type VI choledochal cyst by some authors in the past. We describe a case of a young male with a Type VI choledochal cyst suspected preoperatively on imaging studies and confirmed intraoperatively by laparoscopy. The cyst was localized to the cystic duct with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Type I CCs have the greatest frequency of occurrence (75-85%) compared to other types [1,10]. Isolated cystic dilatation of the cystic duct was added to the Todani classification in 1991 as type VI [11].…”
Section: Discussionmentioning
confidence: 99%
“…Type I CCs have the greatest frequency of occurrence (75-85%) compared to other types [1,10]. Isolated cystic dilatation of the cystic duct was added to the Todani classification in 1991 as type VI [11].…”
Section: Discussionmentioning
confidence: 99%
“…Bresciani et al, 7 Chan et al, 12 and Ray et al 24 have reported on the laparoscopic management of the cystic duct cysts where the most common surgery is a laparoscopic cholecystectomy with cystic duct cyst excision. Laparoscopic cholecystectomy with cyst excision can be done with low threshold for conversion to open cholecystectomy in case of anatomical difficulty and associated biliary anomalies which are seen in most reported cases in literature.…”
Section: Discussionmentioning
confidence: 99%
“…7,9 In 1991, a sixth type, isolated cysts dilation of the cystic duct, was included to the Todani classification. 10 Subsequently, “form fruste” CCs with APBJ and no bile duct dilation were reported. 11…”
Section: Discussionmentioning
confidence: 99%